Clinical validation of the ‘C-arm rotational view (CARV)’: study protocol of a prospective randomised controlled trial - Mostafa El Moumni; Job N Doornberg; Nils Jan Bleeker; Kaj ten Duis; Ruurd L Jaarsma; Frank F A IJpma (BMJ Open, 2023)
Introduction Rotational malalignment occurs in up to 30% of cases after intramedullary nailing of tibial shaft fractures. The aim of this study is to assess the clinical feasibility of a newly introduced standardised intraoperative fluoroscopy protocol coined ‘C-arm rotational view (CARV)’ in order to reduce the risk of rotational malalignment during intramedullary nailing of tibial shaft fractures. The CARV includes predefined fluoroscopy landmark views of the uninjured side to obtain correct alignment of the injured side with use of the rotation of the C-arm.Methods and analysis This randomised controlled trial will be conducted in a level 1 trauma centre. Adult patients with an open or closed tibial fracture, eligible for intramedullary nailing, will be enrolled in the study. The interventional group will undergo intramedullary nailing guided by the CARV protocol to obtain accurate alignment. The control group is treated according to current clinical practice, in which alignment control of the tibia is based on clinical estimation of the treating surgeon. The primary endpoint is defined as the degree of rotation measured on low-dose postoperative CT scans.Ethics and dissemination The study protocol will be performed in line with local ethical guidelines and the Declaration of Helsinki. The results of this trial will be disseminated in a peer-reviewed manuscript. Future patients are likely to benefit from this trial as it aims to provide a clinically feasible and easy-to-use standardised fluoroscopy protocol to reduce the risk for rotational malalignment during intramedullary nailing of tibial shaft fractures.Trial registration number NCT05459038.